2012
DOI: 10.1096/fj.11-198168
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AMP‐metabolizing enzymes controls adenine nucleotide levels and AMPK activation in HEK293T cells

Abstract: We investigated whether overexpression of AMP-metabolizing enzymes in intact cells would modulate oligomycin-induced AMPK activation. Human embryonic kidney (HEK) 293T cells were transiently transfected with increasing amounts of plasmid vectors to obtain a graded increase in overexpression of AMP-deaminase (AMPD) 1, AMPD2, and soluble 5'-nucleotidase IA (cN-IA) for measurements of AMPK activation and total intracellular adenine nucleotide levels induced by oligomycin treatment. Overexpression of AMPD1 and AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
(56 reference statements)
0
20
0
4
Order By: Relevance
“…In contrast, the involvement of AMPD2 and AMPD3, expressed mainly in the liver and erythrocytes, respectively, has been largely overlooked. In HEK293T cells, overexpression of both AMPD1 and AMPD2 slightly decreased AMP levels and oligomycin‐induced AMPK activation . Recently, AMPD2 has been implicated in mediating the toxic effects of high fructose intake .…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 99%
“…In contrast, the involvement of AMPD2 and AMPD3, expressed mainly in the liver and erythrocytes, respectively, has been largely overlooked. In HEK293T cells, overexpression of both AMPD1 and AMPD2 slightly decreased AMP levels and oligomycin‐induced AMPK activation . Recently, AMPD2 has been implicated in mediating the toxic effects of high fructose intake .…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 99%
“…Mitochondrial dysfunction and adenosine signaling could affect pain via activation of AMPK, a protein kinase heavily associated with pain plasticity [93]. Extracellular adenosine, increases in the AMP:ATP ratio during hypoxia, and inhibition of 5′NT all enhance AMPK activity [94,95,96,97]. It is possible that mitochondrial dysfunction within trigeminal pain processing brain regions exacerbates adenosinergic mechanisms and AMPK activity to produce headache.…”
Section: The Role Of Adenosine In Headache Pathophysiologymentioning
confidence: 99%
“…This rise in free AMP upon flight would be more than sufficient to activate AMPK (Pan and Hardie 2002); however, one should bear in mind that AMP concentrations required for activation increase in the presence of free ATP (not complexed with Mg 2+ ) due to competitive binding of the nucleotides to the sites on the AMPKγ regulatory subunits (Gowans et al 2013). Ideally, calculations of free AMP concentrations should be made after measurements of total nucleotides in tissues, as reported in hypoxic goldfish and turtle (Jibb and Richards 2008;Galli et al 2013), and quantification of total nucleotide concentrations by HPLC (Plaideau et al 2012; would be more reliable than enzymatic determinations. Fig.…”
Section: Changes In Adenine Nucleotide Concentrations During Environmmentioning
confidence: 99%
“…It is possible that AMPK might be activated on arousal from hibernation, when fatty acid oxidation is needed for thermogenesis. We showed previously that AMPK activation can be modulated by changes in the activity of AMP-deaminase (AMPD), the AMP-metabolizing enzyme that converts AMP to IMP (Plaideau et al 2012;, and kinetic data suggested that AMPD would be inhibited in muscle of the white-tailed prairie dog during hibernation (English and Storey 2000). A decrease in AMPD2 activity seen in liver could contribute to AMPK activation during hibernation (Lanaspa et al 2015).…”
Section: Ampk Activation In Energy-stressed Animalsmentioning
confidence: 99%